Analysis of reinforcement techniques for partition walls subjected to vertical deformations of concrete slabs - Rui Sousa (2016)
Masonry partitions are non-structural elements that have a fragile behaviour and their interaction with building structures can cause cracking in serviceability conditions, therefore proper techniques/provisions need to be evaluated to avoid cracking in these walls. In this paper a numerical evaluation of some construction/reinforcement techniques to improve the mechanical behaviour of masonry partitions affected by the vertical deformation of concrete slabs were evaluated. This evaluation was made in serviceability conditions, with and without creep effects, through two different approaches: numerical simulation of a concrete structure interacting with unreinforced masonry partitions and numerical simulation of isolated masonry partitions with and without reinforcement techniques. The most common solutions used in Portuguese buildings for structural systems, partition walls and reinforcement techniques were considered: Framed concrete structures, Lightweight clay masonry partitions and reinforcement techniques for masonry walls (reinforcement of bed joints and mortar coatings). The results are presented and discussed and some recommendations are suggested.